On the Completion of Pro-P Groups - Ilić-Georgijević, Emil (Sarajevo Journal of Mathematics, 2024)
We examine the class of finite paragraded groups which we will denote by P. After observing that the class P is closed with respect to subgroups and direct products (7), we define the notion of a pro-P group and consider the completion of such a group. 2000 Mathematics Subject Classification. 08A05, 16W50, 20L05, 20E18, 20-99